2022
DOI: 10.3389/fevo.2022.902412
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Diet of a Predator Using a DNA Metabarcoding Approach

Abstract: The diet of top predators is vital information needed to determine their ecological function and for their conservation management. However, the elusive habit and low population density of many predators constrains determination of their diets. While the morphological identification of scat contents is the traditional method, DNA metabarcoding has lately proven a more efficient and accurate method of identifying prey taxa. We applied DNA metabarcoding to analyzing the diet of the Eurasian otter (Lutra lutra), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…It also confirmed that the drastic decreases in short-tailed shearwater (Puffinus tenuirostris) and little penguin (Eudyptula minor) populations were likely due to Tasmanian devils (McLennan et al, 2022). Eurasian otters (Lutra lutra) were found to have a potentially much more flexible feeding strategy than previously known in western China (Wang et al, 2022). The examination of red fox scats in Scotland found a curiously high percentage of domestic dog (C. l. familiaris) DNA.…”
Section: Application Of Dna Metabarcoding For Species In Other Parts ...mentioning
confidence: 86%
“…It also confirmed that the drastic decreases in short-tailed shearwater (Puffinus tenuirostris) and little penguin (Eudyptula minor) populations were likely due to Tasmanian devils (McLennan et al, 2022). Eurasian otters (Lutra lutra) were found to have a potentially much more flexible feeding strategy than previously known in western China (Wang et al, 2022). The examination of red fox scats in Scotland found a curiously high percentage of domestic dog (C. l. familiaris) DNA.…”
Section: Application Of Dna Metabarcoding For Species In Other Parts ...mentioning
confidence: 86%
“…Hence, eDNA metabarcoding surveys detect a significantly larger proportion of the marine biological community compared to traditional approaches, such as diver surveys (Robinson et al 2023), baited remote underwater video (Stat et al 2019), and trawling (Maiello et al 2022). While a partial overlap in species detection is most commonly observed in comparative experiments with traditional monitoring approaches (Robinson et al 2023), eDNA species detection reliability will further increase when overcoming current limitations, such as enhanced primer design (Wang et al 2023) and more complete reference databases (Stoeckle et al 2020). The application of eDNA metabarcoding, therefore, has the potential to increase species detection efficiency while also offering the advantage of non-invasive sampling to reduce potential disturbances to fragile marine ecosystems (Takahashi et al 2023).…”
Section: Introductionmentioning
confidence: 99%